Taxonomic resolution of the genus Cyanothece (Chroococcales, Cyanobacteria), with a treatment on Gloeothece and three new genera, Crocosphaera, Rippkaea, and Zehria - Mareš, Jan; Johansen, Jeffrey R; Hauer, Tomáš; Zima, Jan; Ventura, Stefano; Cuzman, Oana; Tiribilli, Bruno; Kaštovský, Jan (Journal of phycology, 2019)
The systematics of single-celled cyanobacteria represents a major challenge due to morphological convergence and application of various taxonomic concepts. The genus Cyanothece is one of the most problematic cases, as the name has been applied to oval-shaped coccoid cyanobacteria lacking sheaths with little regard to their phylogenetic position and details of morphology and ultrastructure. Hereby we analyze an extensive set of complementary genetic and phenotypic evidence to disentangle the relationships among these cyanobacteria. We provide diagnostic characters to separate the known genera Cyanothece, Gloeothece, and Aphanothece, and provide a valid description for Crocosphaera gen. nov. We describe two new genera, Rippkaea and Zehria, to characterize two distinct phylogenetic lineages outside the previously known genera. We further describe 13 new species in total including Cyanothece svehlovae, Gloeothece aequatorialis, G. aurea, G. bryophila, G. citriformis, G. reniformis, Gloeothece tonkinensis, G. verrucosa, Crocosphaera watsonii, C. subtropica, C. chwakensis, Rippkaea orientalis, and Zehria floridana to recognize the intrageneric diversity as rendered by polyphasic analysis. We discuss the close relationship of free-living cyanobacteria from the Crocosphaera lineage to nitrogen-fixing endosymbionts of marine algae. The current study includes several experimental strains (Crocosphaera and "Cyanothece") important for the study of diazotrophy and the global oceanic nitrogen cycle, and provides evidence suggesting ancestral N2 -fixing capability in the chroococcalean lineage.
Keywords: endosymbiosis; Nitrogen Fixation; Phylogeny; multilocus analysis; morphology; coccoid cyanobacteria; RNA ribozomální 16S; ultrastructure; RNA, Ribosomal, 16S; Oceans and Seas; sinice; diazotrophy; rRNA ITS region; fylogeneze; 16S rRNA; Cyanothece; Cyanobacteria; oceány a moře; fixace dusíku